Digital-Based Population Service Innovation - Haedar Akib; Syamsiar Syamsiar; Didin Halim; Aris Baharuddin; Alimas Jonsa (Program Pascasarjana Universitas Negeri Makassar, 2024)
In the current VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era, innovation in digital-based public services at the Population and Civil Registry Service (Disdukcapil) is a necessity because it supports increasing the efficiency and effectiveness of services and provides easy access for the public. The article resulting from this research explains the effectiveness of digital-based public service innovations that have been implemented at the Polewali Mandar District Dukcapil Office in improving service quality. The type of research used is qualitative with a case study approach to describe, analyze, and explain innovation at the research locus. Data, information, and knowledge were collected using observation, interview, and documentation techniques. The data was analyzed following the interactive model stages which include data collection, data condensation, data presentation, and conclusion drawing/verification. The research results show that the Population and Civil Registry Service in Polewali Mandar Regency implements digital-based public service innovations effectively because they are consistent with the demands and needs of the service user community. Systematic steps such as monitoring, evaluation, outreach, and analysis of service user satisfaction have also been carried out effectively and regularly to improve understanding and quality of services. Based on government commitment, community acceptance, and the selection of appropriate technology, this population's public service innovation can provide maximum benefits for all interested parties.